2017
DOI: 10.3389/fimmu.2017.01674
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microbiota on Intestinal Immune System in Ulcerative Colitis and Its Intervention

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) with chronic and recurrent characteristics caused by multiple reasons. Although the pathogenic factors have not been clarified yet, recent studies have demonstrated that intestinal microbiota plays a major role in UC, especially in the immune system. This review focuses on the description of several major microbiota communities that affect UC and their interactions with the host. In this review, eight kinds of microbiota that are highly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 163 publications
(168 reference statements)
0
68
0
Order By: Relevance
“…Additionally, fecal levels of several commensal bacteria, including Veillonella spp., E. coli, and Fusobacterium spp., were positively associated with inflammation biomarkers in the current study. All of those bacteria were considered as invasive [38][39][40], and high levels were reported previously in IBD patients [23,28,31,33,[41][42][43][44][45]. Changes in Prevotella spp.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, fecal levels of several commensal bacteria, including Veillonella spp., E. coli, and Fusobacterium spp., were positively associated with inflammation biomarkers in the current study. All of those bacteria were considered as invasive [38][39][40], and high levels were reported previously in IBD patients [23,28,31,33,[41][42][43][44][45]. Changes in Prevotella spp.…”
Section: Discussionmentioning
confidence: 98%
“…3D , where we found phenotypes related to inflammation were driven by high-divergence genes. Furthermore, we find that Eubacterium rectale and B. ovatus , microbes that have higher abundance in humans and that have been previously associated with inflammatory bowel disease (Noor et al, 2010;Zhang et al, 2017) , upregulate the expression of CSF3 , which has been reported as upregulated in ulcerative colitis patients (de Lange & Barrett, 2015;Hotte et al, 2012) To investigate specific host gene-pathway interactions, we constructed a network of the most significant interactions between microbial pathways and high-divergence host genes as described above ( Fig 4E ; see Methods). We find that nine of these 17 host genes, including DUSP5 , CYR61 , NFKBIZ , PTGS2 , IL6 , CXCL8 , IL36G , IL1B , and IL36RN (all displayed at the top layer in Fig.…”
Section: Examples Of Several Microbes That Have Variable Abundance Acmentioning
confidence: 98%
“…Gut microbiota is considered to be an critical factor in deriving ulcerative colitis (UC) [1,2,3], which is characterized by abnormal microbiota leading to disruption of ora balance, decreasing the complexity of the intestinal microbial ecosystem [4]. At the same time, UC is thought to be caused by an imbalance between intestinal microbiota and mucosal immunity [5].…”
Section: Introductionmentioning
confidence: 99%